1996
DOI: 10.1111/j.1467-8624.1996.tb01869.x
|View full text |Cite
|
Sign up to set email alerts
|

Intention, Act, and Outcome in Behavioral Prediction and Moral Judgment

Abstract: 72 children at 3, 4, and 5 years of age and 24 undergraduates were required to use information about intention under a normal causal system or a noncanonical one (e.g., hitting causes pleasure) to predict an agent's behavior. Additionally, they were asked to integrate intentions, acts, and outcomes to judge an act's acceptability and assign punishment. 3‐year‐olds performed poorly on behavioral prediction in the noncanonical condition. Most participants at all ages made categorical judgments of act acceptabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
78
1
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 55 publications
7
78
1
2
Order By: Relevance
“…Does a dog intend to hurt when it bites another dog that tries to take its food away?Does a 12-month-old boy intend to hurt when he hits the peer who grabbed the toy in his hand? The age of ''onset'' of intent may have been clear to Kagan in 1974, but it is still a subject of debate (Diamond, Werker, &Lalonde, 1994;Flavell &Miller, 1998;Zelazo, Helwig, & Lau, 1996). The intent criteria is not only a problem for infants and nonhuman animals.…”
Section: Intent To Harmmentioning
confidence: 99%
“…Does a dog intend to hurt when it bites another dog that tries to take its food away?Does a 12-month-old boy intend to hurt when he hits the peer who grabbed the toy in his hand? The age of ''onset'' of intent may have been clear to Kagan in 1974, but it is still a subject of debate (Diamond, Werker, &Lalonde, 1994;Flavell &Miller, 1998;Zelazo, Helwig, & Lau, 1996). The intent criteria is not only a problem for infants and nonhuman animals.…”
Section: Intent To Harmmentioning
confidence: 99%
“…When moral scenarios present conflicting information about the outcome of an action and the intention of the actor, young children's moral judgments and justifications are determined by the action's outcome rather than the actor's intention (9)(10)(11)(12)(13). For example, a person who intends to direct a traveler to the right location but accidentally misdirects him is judged by young children to be ''naughtier'' than a person who intends to misdirect a passerby but accidentally directs him to the right place (9).…”
mentioning
confidence: 99%
“…Although subsequent research has revealed that young children can use information about intentions to make moral distinctions when consequences are held constant between scenarios (14,(20)(21)(22)(23), older children have consistently shown greater sensitivity to information about intentions. What develops then is not just ''theory of mind,'' or the ability to represent the mental states of others, but the ability to integrate this information with information about consequences in the context of moral judgment (12,13,24,25).…”
mentioning
confidence: 99%
“…Accordingly, it remains for future research to examine how children younger than age 9 would assign moral status. Given the intimate connection between the concept of harm and the ability to suffer, and given the fact that the concept of harm occupies a central place in the moral thinking of even 3-year-old children (Zelazo et al, 1996), it might be expected that even much younger children use the ability to suffer as a criterion for moral status assignment.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore not surprising that much research on the development of moral awareness has focused on how the moral judgments of children and adults about a perpetrator's doings are affected by (1) the perpetrator's responsibility for harming the victim and (2) the severity of the harm that is caused (e.g. Piaget, 1932;Yuill, 1984;Zelazo, Helwig, & Lau, Children and adults are known to attribute both mental capacities to at least some non-human entities (Coley, 1995;Knight, Nunkoosing, Vrij, & Cherryman, 2003), but what evidence is there that they acknowledge the moral relevance of both types of attributions? The examples given by Kahn (2006) suggest that at least some children acknowledge the moral relevance of the ability to suffer.…”
mentioning
confidence: 99%